Klasifikasi Emosi Lirik Lagu menggunakan Improved K-Nearest Neighbor dengan Seleksi Fitur dan BM25 - Febrina Sarito Sinaga; Indriati Indriati; Bayu Rahayudi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Emotions is a person's reaction or feeling into a situation. Emotion is temporary that can occurred by a stimulus because of some people around and the environment. One of example an environment that can trigger someone's emotion is from the song being listened to. Song lyrics are the parts that can build emotions. Choosing the right words for lyrics are very important because it will create the right emotion. In this case the emotional classification of song lyricis will be done classifying process using several methods are Improved K-Nearest Neighbor, BM25 and feature selection. The proses of classification have seome stages, which is the stage of pre-processing documents, stages of calculation the BM25 score and sorting document, and the classification stage with using the algorithm is Improved K-Nearest Neighbor. The testing for classifications was done uses 6 times K-fold and use the confusion matrix. This research is the amount of training data used by 100 documents, and testing data used by 20 testing documents. In the all the tests have done obtained the best average results when the value K = 55 with a result of f-measure is 0.6693, recall is 0.6582, and precision is 0.7427.